EFFICIENT CLOUD STORAGE USING DATA PARTITION AND TIME BASED ACCESS CONTROL WITH SECURE AES ENCRYPTION TECHNIQUE - P.Pandiaraja, K.Aravinthan, R.Lakshmi Narayanan, K.S.Kaaviya, K.Madumithra (International Journal of Advanced Science and Technology, 2020)
Cloud Computing (CC) links the computing plus storage data’s measured by diverse operating systems towards create accessible services for example huge scaled data storage and extraordinary performance computing to users. The info outsourced towards a public cloud that want to be protected. Appropriately, encrypted outsourced documents cannot be deduplicated. The Deduplication system is used to progress storage operation and can moreover functional to network data transmissions to decrease the amount of bytes that need be sent. Uploaded data was divided into lumps and that are related to the stored replica and whenever a match occurs, the redundant chunk is substituted with a minor reference that opinions to the stored chunk. This proposed work achieves Division plus Replication of Data (DROPs) within the Cloud for Optimal Performance and Security that judicially fragments user uploaded documents into dissimilar portions also replicates them at dissimilar places in the cloud server. The separation of a files into manifold fragments is accomplished based on a given consumer criteria such that the discrete fragments do not discloses any significant truths. The node splitting procedure is confirmed by the means of Grid Topology algorithm. To add progress in the retrieval time, replicate the data fragments above the nodes that produce the highest read/write requests. The data encrypted using AES algorithm